Solve it step by step
Attachments:
![](https://hi-static.z-dn.net/files/d25/7cb2741df6b3f5c8e0a67b672c6b0386.jpg)
Answers
Answered by
0
6x+9=8
6x=8-9
6x=-1
x= -1/6
6x=8-9
6x=-1
x= -1/6
robel12:
thanks
Answered by
0
Hey user, here is your answer...
____________________________________
![6x + 9 = 8 \\ = > 6x = 8 - 9 \\ = > 6x = - 1 \\ = > x = - \frac{1}{6} 6x + 9 = 8 \\ = > 6x = 8 - 9 \\ = > 6x = - 1 \\ = > x = - \frac{1}{6}](https://tex.z-dn.net/?f=6x+%2B+9+%3D+8+%5C%5C+%3D+%26gt%3B+6x+%3D+8+-+9+%5C%5C+%3D+%26gt%3B+6x+%3D+-+1+%5C%5C+%3D+%26gt%3B+x+%3D+-+%5Cfrac%7B1%7D%7B6%7D+)
____________________________________
Hope it helps.
Thanks for the question.
____________________________________
____________________________________
Hope it helps.
Thanks for the question.
Similar questions